2017
DOI: 10.1590/s0100-736x2017000400006
|View full text |Cite
|
Sign up to set email alerts
|

Minimum inhibitory concentration of Brazilian Brachyspira hyodysenteriae strains

Abstract: The objectives of this study were to characterize Brachyspira hyodysenteriae isolates and to evaluate the antimicrobial susceptibility patterns of strains obtained from pigs in Brazil based on the minimal inhibitory concentration test (MIC). The MIC was performed for 22 B. hyodysenteriae isolates obtained from 2011 to 2013 using the following antimicrobial drugs: tylosin, tiamulin, valnemulin, doxycycline, lincomycin and tylvalosin. Outbreaks of swine dysentery were diagnosed based on clinical presentation, ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Strains of Brachyspira spp. resistant to commonly used antimicrobials have been detected in several studies (Duinhof et al 2008, Pringle et al 2012, and, recently, in Brazil in a investigation that evaluated the sensitivity of Brachyspira hyodysenteriae and Brachyspira pilosicoli to different classes of antimicrobials (Daniel et al 2017). Brachyspira species may survive in organic material, such as feces diluted in water, for as long as 48 days in environmental temperatures ranging from 0 to 10°C (Hampson & Burrough 2019); however, this study has detected a higher incidence of clinical disease during spring/summer, which may have occurred because of a higher infection pressure, as well as due to problems of bay drainage and asymptomatic pigs acting as carriers and infection sources (Hampson & Burrough 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains of Brachyspira spp. resistant to commonly used antimicrobials have been detected in several studies (Duinhof et al 2008, Pringle et al 2012, and, recently, in Brazil in a investigation that evaluated the sensitivity of Brachyspira hyodysenteriae and Brachyspira pilosicoli to different classes of antimicrobials (Daniel et al 2017). Brachyspira species may survive in organic material, such as feces diluted in water, for as long as 48 days in environmental temperatures ranging from 0 to 10°C (Hampson & Burrough 2019); however, this study has detected a higher incidence of clinical disease during spring/summer, which may have occurred because of a higher infection pressure, as well as due to problems of bay drainage and asymptomatic pigs acting as carriers and infection sources (Hampson & Burrough 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Two possible explanations may be applied to this increase in number of cases of Brachyspira spp. colitis: it may be related to a bacterial resistance to some of the antimicrobials commonly applied to control clinical disease; or it may have occurred due to the introduction of clinically health females, which could have carried subclinical infections to many sow farms of different integration companies (Daniel et al 2013, Daniel et al 2017. Strains of Brachyspira spp.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing the antimicrobial susceptibility profiles of U.S B. hyodysenteriae isolates to those reported internationally, our findings suggest that, overall, U.S B. hyodysenteriae isolates are more susceptible to antimicrobials. Mainly, the U.S. B. hyodysenteriae isolates are more susceptible to tiamulin than the isolates from the United Kingdom, 17 Italy, 31 Poland, 38 Germany, 13,17 the Czech Republic, 32 Brazil, 6 Japan, 16 and Spain. 12 However, it is worth noting that, in Europe, there are limited antimicrobials available for the treatment of SD.…”
Section: Discussionmentioning
confidence: 95%
“…In Latin America, limited studies were carried out concerning the presence of different species of Brachyspira. In Brazil, some regional studies identified B. hyodysenteriae and B. pilosicoli in pigs [11,12]. In Mexico, strongly and weakly hemolytic spirochetes were identified in 22% of pig farms [13].…”
Section: Introductionmentioning
confidence: 99%